Creativity 34 : bright ideas in advertising and design from around the world - Carter, David E. (New York : Collins Design, 2005)
Someone recently asked me "How is Creativity different from the other annuals?" Creativity isn't limited to certain zip codes, or to certain countries. Creative work, even when it comes from global ad agencies, is usually the product of a small handful of people-- creative people. Creative excellence is all about the idea and the execution. And that's what is different about Creativity 34. Here, you'll see work from global agencies in New York, London, and Seoul, and other advertising centers around the world. You'll also see work from highly creative small firms, from Bangkok and Birmingham to Charleston and Copenhagen. Creativity is a state of mind. And excellent work is shown in Creativity, no matter where it comes from. That's how we're different.
Includes index
Keywords: Commercial art